2000
DOI: 10.4049/jimmunol.164.12.6380
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Germline Promoters by the Two Human Ig Heavy Chain 3′ α Enhancers

Abstract: The human IgH 3′ enhancers, located downstream of each of the two Cα genes, modulate germline (GL) transcription of the IgH genes by influencing the activity of promoter-enhancer complexes upstream of the switch and intervening (I) regions. The regulation of GL α1 and α2 promoters by different human 3′ enhancer fragments was investigated in cell lines representing various developmental stages. Both α1HS1,2 and α2HS1,2 fragments show equally strong enhancer activity on the GL α1 and α2 promoters in both orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Although other studies had shown that human 3Ј enhancers were inactive or poorly active (Ͻ4-fold), in human mature B cell lines (18,25) these differences can be attributed to differences in promoter usage and/or efficiencies of transfection. The contribution of NF-B and octamer binding sites to human hs4 enhancer activity a Data are shown as fold activity with respect to the enhancerless constructs.…”
Section: Synergistic Binding To Nf-b and Octamer Sites Controls The Amentioning
confidence: 99%
See 1 more Smart Citation
“…Although other studies had shown that human 3Ј enhancers were inactive or poorly active (Ͻ4-fold), in human mature B cell lines (18,25) these differences can be attributed to differences in promoter usage and/or efficiencies of transfection. The contribution of NF-B and octamer binding sites to human hs4 enhancer activity a Data are shown as fold activity with respect to the enhancerless constructs.…”
Section: Synergistic Binding To Nf-b and Octamer Sites Controls The Amentioning
confidence: 99%
“…Because targeted deletion of hs3A, which is virtually identical with that of hs3B (16), showed no effect on isotype expression (14), hs4 is likely to play a unique role in this phenotype. In support for a role of 3Ј enhancers in germline transcription, transient transfection assays have shown that both mouse (17) and human (18,19) 3Ј enhancers augmented I region-driven reporter constructs. A role for hs3 and/or hs4 in somatic hypermutation has also been suggested (20); however, the targeted deletion of hs3B and hs4 revealed no effect on somatic hypermutation (21).…”
Section: T He Expression Of Ig H Chain (Igh)mentioning
confidence: 99%
“…The role of the complex regulative region in Ig transcription and in the path of maturation of B lymphocytes is not definitively known (Hu et al, 2000;Saleque et al, 1999). Several transcription factors have been shown to be necessary for B cell maturation (Conley, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Both regions are involved in class switch and consequently in B lymphocytes maturation (9). These duplicated LCRs at the 3' of both C alpha-1 and C alpha-2 genes, shown in Fig.…”
mentioning
confidence: 99%